A study of male fertility control in Medicago truncatula uncovers an evolutionarily conserved recruitment of two tapetal bHLH subfamilies in plant sexual reproduction. Issue 3 (25th July 2020) - Zheng, Xiaoling; He, Liangliang; Liu, Ye; Mao, Yawen; Wang, Chaoqun; Zhao, Baolin; Li, Youhan; He, Hua; Guo, Shiqi; Zhang, Liangsheng; Schneider, Harald; Tadege, Million; et al.
Summary: Male sterility is an important tool for plant breeding and hybrid seed production. Male‐sterile mutants are largely due to an abnormal development of either the sporophytic or gametophytic anther tissues. Tapetum, a key sporophytic tissue, provides nutrients for pollen development, and its delayed degeneration induces pollen abortion. Numerous bHLH proteins have been documented to participate in the degeneration of the tapetum in angiosperms, but relatively little attention has been given to the evolution of the involved developmental pathways across the phylogeny of land plants. A combination of cellular, molecular, biochemical and evolutionary analyses was used to investigate the male fertility control in Medicago truncatula . We characterized the male‐sterile mutant empty anther1 ( ean1 ) and identified EAN1 as a tapetum‐specific bHLH transcription factor necessary for tapetum degeneration. Our study uncovered an evolutionarily conserved recruitment of bHLH subfamily II and III(a + c)1 in the regulation of tapetum degeneration. EAN1 belongs to the subfamily II and specifically forms heterodimers with the subfamily III(a + c)1 members, which suggests a heterodimerization mechanism conserved in angiosperms. Our work suggested that the pathway of two tapetal‐bHLH subfamilies is conserved in all land plants, and likely was established before the divergence of the spore‐producing land plants.